2013
DOI: 10.4103/0019-5545.111454
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric symptoms in mild cognitive impairment: An analysis and its impact on caregiving

Abstract: Background:Neuropsychiatric impairments play a significant role throughout the course of cognitive decline. Many psychological and behavioral symptoms are present in patients of mild cognitive impairment (MCI) similar to that seen in individuals with dementia.Aims and Objectives:To study the relevance of neuropsychiatric symptoms of MCI and the impact it has on caregivers of these patients.Materials and Methods:This cross-sectional study was done on 90 patients (30 MCI, 30 dementia and 30 controls) above the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…These studies also reported that MCI patients with behavioural disturbances are more likely to develop AD than patients without these features. Furthermore, Trivedi et al [123] reported that neuropsychiatric symptoms (as measured by the NPI) were significantly more severe and frequent in patients with MCI than in healthy participants, and demented patients had significantly more neuropsychiatric problems than MCI and healthy groups. Other studies have shown that there was a negative association between frequency of neuropsychiatric symptoms and MMSE scores in patients with MCI [120,122].…”
Section: Discussionmentioning
confidence: 99%
“…These studies also reported that MCI patients with behavioural disturbances are more likely to develop AD than patients without these features. Furthermore, Trivedi et al [123] reported that neuropsychiatric symptoms (as measured by the NPI) were significantly more severe and frequent in patients with MCI than in healthy participants, and demented patients had significantly more neuropsychiatric problems than MCI and healthy groups. Other studies have shown that there was a negative association between frequency of neuropsychiatric symptoms and MMSE scores in patients with MCI [120,122].…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers frequently report that communication with ward staff is inadequate . Behavioral disturbance in patients has long been associated with poor psychological health in caregivers . Quality of care, behavioral disturbance, caregiver strain, and dissatisfaction are likely to have a complex interrelationship.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding corroborates observation of another study done using NPI which found distress caused by neuropsychiatric symptoms is significantly more in caregivers of MCI than HC group. [20] As per Engelborghs et al classification of BEHAVE-AD scores, MCI group had mild behavioral symptoms whereas HC group has none. Study by S. Van der Mussele et al [21] observed the prevalence and severity of frontal lobe symptoms, physical and verbal aggressiveness, activity disturbances, and delusions were intermediate between normal aging and AD in their comparative study of MCI, AD and normal subjects.…”
Section: Behavioural Symptoms In Patients With MCI and Healthy Comentioning
confidence: 91%